Образи «місто» і «село» як фрагменти мовоопису чорнобильського простору - Гоцинець, І. (Культура слова, 2021)
У статті запропоновано лінгвостилістичний аналіз образів «місто» і «село» як фрагментів чорнобильського простору. Окрему увагу звернено на епітетне моделювання обра- зів. Зокрема, встановлено, що родові номінації місто, село, а також назви конкретних населених пунктів, які найбільше постраждали від аварії на ЧАЕС, послідовно поєднуються з негативно-оцінними епітетами безлюдний, малолюдний, порожній, спорожнілий, покинутий, мертвий, недоглянутий, осиротілий, які вербалізують семантику ‘відсутність життя’, ‘завмирання життя’, ‘безлюддя’. Відзначено стилістичну актуальність означень заражене, приречене, неперспективне – як епітетних характеристик поставарійних населених пунктів. У контексті розгляду механізмів асоціативно-семантичного розвитку мотиву «покинуті, мертві міста і села у зоні відчуження» відзначено текстотвірну вагомість негативно-оцінних образів із семою ‘тиша’, модальних слів нема, немає, заперечних займенників та прислівників (ніхто, нікого, нікому, ніде), дієслівних конструкцій із заперечними частками не та ні, конструкцій із прийменником без. Images of cities and villages for which the consequences of the Chornobyl explosion became the most tangible are outlined in Ukrainian artistic discourse with documentary authenticity. These descriptions exacerbate emotionality, the tone of tragedy, and sometimes apocalyptic coloration. The general nominations city, village, as well as the names of specific settlements that have suffered the most from the Chоrnobyl accident, are consistently combined with the negative epithets deserted, sparsely populated, empty, empty, abandoned, dead, neglected, orphaned. Verbalizing the semantics of ‘lack of life’, ‘fading of life’, ‘desolation’, they depict and assess the state of towns and villages after the accident, in particular in connection with the situation of mass evacuation of residents. The expressiveness of the description is intensified by the definitions of abandoned, neglected, orphaned. The overall picture of desolation is visually complemented by images of looted homes, wild pets, overgrown fields and gardens. The verbal image of a radiation-infected town / village is especially relevant for the texts of fiction and non-fiction. The authors quite motivatedly characterize post-accident cities with the help of epithets infected, doomed, unpromising. The associative-semantic deepening of the motif “abandoned, dead towns and villages in the exclusion zone” is provided by negative-evaluation images with the seed ‘silence’. In the linguistic portraitl of empty, uninhabited towns and villages, modal words no, no, negative pronouns and adverbs (nobody, nowhere) and verb constructions with negative particles no and no, constructions with a preposition without perform an important text-forming function. Indicative aspect of the description - the space above the city, the sky. This is objectively motivated by the artistic reflection of the fact that the cloud of radioactive contamination formed as a result of the explosion rose up, covering Chоrnobyl and Pripyat. The tension of the «ground» atmosphere in Pripyat and Chernobyl is described by verbs and verb compounds with the seeds ‘intensive traffic’, which metaphorize the intensity of traffic – to take off, snatch, race, fly, tear / jerk, jump. Together, they create a cinematic description characteristic of chronicle-documentary prose. This is facilitated by verbs with the seeds ‘to move quickly’, ‘to stop suddenly’, ‘to start moving suddenly’.